Failure modes, causes, and effects of algal photobioreactors used to control a spacecraft environment. (February 2019) - Matula, Emily E.; Nabity, James A.
Abstract: Bioregenerative technologies, in particular algae photobioreactors, have the potential to provide closed-loop environmental control and life support for human space flight, if robust enough for long-duration deep space missions. This paper reviews the failure modes, causes, and effects of an algal photobioreactor system for use in space flight environmental control and life support applications. The likelihood and severity for each failure is estimated, and associated mitigation or contingency plans are described. Failure modes can stem from either the algae cellular physiology or the engineered system needed for the application and are grouped in this paper accordingly.